PERPETUAL POLEMOS: WAR PROFITEERING IN ASSASSIN'S CREED ODYSSEY - Haryo Pambuko Jiwandono (Brawijaya Journal of Social Science, 2020)
Assassin’s Creed Odyssey; the newest entry in Assassin’s Creed series, provides interesting expressions of historical dominant Ancient Greece. The most unique and outstanding aspects of its expressions are those of war profiteering in Ancient Greece and its intersection with modern concepts and processes of war profiteering. Through textual analysis of the game’s sign systems and rules, it is discovered that this game also strongly enforces perpetuated violent methods as means of profiteering through codification of those methods into key ludic rules of the game which create dissonance between its story and its gameplay. Finally, this research is expected provide new insight about expressions of union between violence and profit making in digital games.